Certified Kubernetes Administrator (CKA) : complete video course - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2023)
8 hours of deep dive training to learn everything needed to pass the CKA exam. Get the edge you need to successfully study for and pass the Certified Kubernetes Administrator (CKA) exam in this all-new video course. This 3rd edition acts as a complete study resource to help you build skills as you work your way through the course. Explore each exam objective on the CKA exam and learn how to build, run, and manage Kubernetes clusters. Expert trainer and author Sander van Vugt gives you hands-on labs to work with Kubernetes, so you have the opportunity to test your skills. The course then ends with a sample exam, allowing you to practice before taking the real thing. The Certified Kubernetes Administrator (CKA) Complete Video Course introduces containers and Kubernetes, and moves through the process of creation, managing, and storing applications before providing labs on setting up and managing clusters, and how to troubleshoot Kubernetes applications and cluster nodes. Sander shows how to manage deployments, services, ingress, setting up storage, and walks through key troubleshooting scenarios.